Efficient and switchable aptamer "fluorescence off/on" method based on UiO-66@Cu for ultrasensitive detection of acetamiprid. Issue 4 (August 2022) - He, Kangli; Dong, Sa; Yang, Jinghan; Shi, Qiuyun; Guan, Lingjun; Sun, Li; Chen, Zhiyang; Feng, Jianguo
Abstract: Acetamiprid (ACE) is one of the primary pesticides used to control sucking-mouthpart pests, such as aphids, thrips, and whiteflies. However, owing to its internal absorption characteristics, ACE can easily form pesticide residues that harm human health and cause environmental pollution. Therefore, it is extremely important to establish an ultrasensitive, accurate, and rapid method to detect ACE and limit ACE residues within a specific range. In this study, a bilayer metal-organic framework UiO-66 @Cu was synthesized using a simple hydrothermal method, and a "fluorescence off/on" strategy was constructed for ACE detection. The FAM-modified aptamer (Apt-FAM) absorbed onto the UiO-66 @Cu surface via electrostatic interactions and the fluorescence of Apt-FAM to be quenched by UiO-66 @Cu through photoelectron transfer between UiO-66 @Cu and FAM. In the presence of ACE, it is tightly bound to Apt-FAM, drawing it away from theUiO-66 @Cu surface, and the fluorescence intensity of the entire system was restored. The results indicated that under the optimal conditions, the limit of detection (LOD) and linear range of the "fluorescent off/on" method were 0.36 μg/mL and 0.5–10 μg/mL, respectively. The method exhibits good sensitivity, selectivity and reproducibility, which provides an original approach for the direct detection of ACE. Graphical Abstract: ga1 Highlights: A bimetallic organic framework UiO-66 @Cu was successfully synthesized. A "fluorescence off/on" method based on UiO-66 @Cu was constructed and used for ACE detection. Achieving the detection of ACE as low as 0.36 μg/mL. The constructed method can be used for ACE detection in complex environment.